347 Cancer-associated Fibroblasts Affect GBM Progression. (1st April 2022) - Kim, Timothy Y.; Srivastava, Siddhartha; Medikonda, Ravi; Pant, Ayush; Patel, Kisha K.; Rodriguez, Fausto; Lim, Michael
Abstract : INTRODUCTION: Glioblastoma is an extremely aggressive form of brain cancer and despite the many advances made in therapeutic options, outcome and quality of life remains poor. Fibroblasts have been demonstrated to play a role in various systemic cancers by remodeling and reprogramming the tumor microenvironment immunologically and metabolically. Recently, cancer-associated fibroblasts (CAFs) have been identified in glioblastoma (GBM) patients and there is reason to believe that CAFs may have a protumoral effect in GBM progression. METHODS: Nine patients with resected GBM tumor samples were identified by pathology reports and embedded in paraffin, sectioned, and then stained with antibodies for alpha-SMA and GFAP. Ten 40x high-power fields per slide were visualized by a Zeiss Axio Observer microscope and counted by two independent researchers and verified by a board-certified neuropathologist. For in vivo work, 6-week C57BL/6J wild-type female mice were intracranially implanted with either Gl261-luciferase (Gl261-luc) tagged cells alone or in combination with NIH3T3 embryonic fibroblasts. Tumor burden was assessed on post-implantation day 7 via bioluminescent IVIS imaging. RESULTS: We found that fibroblasts were consistently present in human glioblastoma samples albeit in minute quantities of <1%. We then discovered on IVIS that Gl261 cells mixed with NIH3T3 fibroblasts produced larger tumors on day 7 post-implantation. Implantation of these exogenous fibroblasts significantly worsened survival although this effect was not dose-dependent. CONCLUSION: Fibroblasts are present in glioblastoma patient samples. Despite their scarcity, they may still have the ability to affect the tumor microenvironment. Exogenous intracranial implantation of fibroblasts led to increased proliferation of gl261-luc tumor cells. As expected, these larger tumors had a negative effect on mouse survival and suggest that fibroblasts may be a potential avenue of glioblastoma therapy that needs further exploration.